Mn-doped ZnO nanopowders prepared by sol–gel and microwave-assisted sol–gel methods and their photocatalytic properties - Cristina Maria Vlăduț; Crina Anastasescu; Silviu Preda; Oana Catalina Mocioiu; Simona Petrescu; Jeanina Pandele-Cusu; Dana Culita; Veronica Bratan; Ioan Balint; Maria Zaharescu (Beilstein Journal of Nanotechnology, 2024)
Although the microwave-assisted sol–gel method is quite frequently used for the preparation of oxide nanostructures, the synergism of the reaction pathways is not fully explained. However, state-of-the-art theoretical and practical results of high novelty can be achieved by continuously evaluating the as-synthesized materials. The present paper presents a comparative study of Mn-doped ZnO nanopowders prepared by both sol–gel and microwave-assisted sol–gel methods. The structural, morphological, and optical properties of the as-obtained powders were established and correlated with their newly proved functionality, namely, the ability to photogenerate distinct reactive oxygen species (·OH or O2−) and to act as photoactive materials in aqueous media. The solar light-induced mineralization of oxalic acid by Mn-doped ZnO materials was clearly observed while similar amounts of generated CO2 were measured for both catalysts. These inexpensive semiconductor materials, which proved to be light-responsive, can be further used for developing water depollution technologies based on solar light energy.